Komponen yang Berpengaruh terhadap Peningkatan Nilai Perusahaan Manufaktur - Desy Nur Pratiwi (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2021)
This study aims to obtain empirical evidence of the impact of profitability, firm growth, firm size and tax avoidance on firm value. The population taken by the researcher is the manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sampling method chosen was purposive sampling and that met the criteria of 43 companies. The analysis technique used is multiple linear regression. The results of the empirical test are profitability, firm growth, firm size have a positive influence on firm value, but tax avoidance has no effect on firm value.